PERAN FOOD AND AGRICULTURE ORGANIZATION (FAO) DALAM MENINGKATKAN KETAHANAN PANGAN SEBAGAI UPAYA UNTUK MENANGANI KRISIS KELAPARAN DI SAHEL TAHUN 2013-2015 - Afifah Rizqy Widianingrum; Reni Windiani; Fendy Eko Wahyudi (Journal of International Relations Diponegoro, 2023)
This research aims to describe the role of FAO as an international organization in increasing food security as an effort to deal with the hunger crisis in the Sahel in 2013-2015. This research based on 2013-2015, the Sahel region was hit by a food insecurity crisis. Poor food conditions occur due to a variety of complex factors such as a prolonged drought which has an impact on drought, soil degradation and erosion, outbreaks, and internal conflicts. As a result, people have limited access to nutritious food and experience acute malnutrition. Thus, efforts to overcome the hunger crisis in the Sahel region really need to be done. This aims to reduce the increasing number of hunger and death. If there is no support, the community will have to live without adequate food and nutrition stocks. Therefore, international organizations exist to deal with the current hunger crisis, one of which is the Food and Agriculture Organization (FAO). Using the theory of liberalism and the concept of international organizations which are derivatives of liberalism, this research analyses the Sahel region. The result shows that FAO has a role to play in increasing food security in the Sahel region in overcoming the food crisis that occurred in 2013-2015.